The Impact of Diglossia on Voweled and Unvoweled Word Reading in Arabic: A Developmental Study From Childhood to Adolescence. (3rd July 2016) - Saiegh-Haddad, Elinor; Schiff, Rachel
ABSTRACT: All native speakers of Arabic read in a language variety that is remarkably distant from the one they use in everyday speech. The study tested the impact of this distance on reading accuracy and fluency by comparing reading of Standard Arabic (StA) words, used in StA only, versus Spoken Arabic (SpA) words, used in SpA too, among Arabic native speakers in Grades 2, 4, 6, 8, and 10 ( N  = 100). Pseudowords in SpA and StA were also compared. Analysis of variance results revealed significant differences in reading SpA versus StA words across all grades and in reading voweled and unvoweled words. The findings support the effect the linguistic distance between SpA and StA on word reading development.